PRINCIPAL COMPONENT ANALYSIS (PCA) OF THE ACTIVITIES OF INFORMAL CONSTRUCTION WORKERS/ARTISANS IN NIGERIA - Sunday Julius Odediran; Olubola Babalola (Journal of Construction Project Management and Innovation)
Every employment has deposit of activities to be performed by her employees. These activities vary with industries and who performs each of these activities is determined by how significance they are to the employment operation. Construction is one of such industries whose activities necessitate the growth and development of infrastructure needs of the societies. The activities in the construction industry are performed by different trades’ artisans refer to as informal workers/artisans in this paper. Hence, this paper examines the activities of informal construction workers/artisans in Nigeria with a view to classify these activities according to various trades in the industry. A comprehensive list of construction activities was made and informal workers/artisans were asked to rank these activities based on the frequency of how they are being performed on construction projects. Data collected were analyzed using factor analysis which classified these activities into principal components that described construction trades. The result of the study shows that the most frequent activities are associated with demolition & reconstruction and woodwork while the least frequent activities associated with electrical works. The result also classifies activities in the industry into various trades including plumbing installations, mansory & blockwork, steelworks, woodworks, electrical installations, painting & decoration; and demolition & reconstruction. The finding of this study provides information on the activities of the informal workers/artisans in the construction industry for the professionals, employers and policy makers to provide enabling and friendly environment for efficient service delivery in the construction industry.